Effect of the CYP3A inhibitor ketoconazole on the PXR-mediated induction of CYP3A activity - Fuchs, Ines Verena; Hafner-Blumenstiel, Verena; Markert, Christoph; Burhenne, Jürgen; Weiß, Johanna; Haefeli, Walter E.; Mikus, Gerd (European journal of clinical pharmacology, 2013)
Purpose: The aim of this clinical study was to investigate a previously proposed mechanism of ketoconazole-mediated inhibition of cytochrome P450 3A (CYP3A) induction.MethodsA two-phase, randomized, cross-over, open, mono-centre trial was carried out. Participants received ketoconazole and St John’s wort for 8 days to study the proposed suppression of St John’s wort-mediated induction of CYP3A at the transcriptional level. In the second phase, we studied the inhibitory effect of a single dose of ketoconazole directly at the enzyme level during CYP3A induction by St John’s wort. Midazolam served as a marker substance of CYP3A activity using an established limited sampling strategy. Results: After 8 days of simultaneous ketoconazole and St John’s wort administration, CYP3A-mediated midazolam metabolism was strongly inhibited (81 % decrease in clearance). Following the induction of CYP3A with St John’s wort (6.6-fold increase in clearance on day 8), a single dose of ketoconazole strongly inhibited midazolam metabolism to the same degree (82 % decrease in clearance in relation to baseline). An induction of midazolam metabolism was observed after discontinuation of both drugs in both study phases. These results apparently contradict the in vitro results where ketoconazole showed an inhibitory effect on the transcription of CYP3A genes.Conclusions: Ketoconazole is a strong inhibitor of CYP3A, also when used concomitantly with St John’s wort. In therapeutic doses it does not inhibit pregnane X receptor-mediated induction of CYP3A in vivo.